The unnameables - Booraem, Ellen (Harcourt, 2008)
On an island in whose strict society only useful objects are named and the unnamed are ignored or forbidden, thirteen-year-old Medford encounters an unusual and powerful creature, half-man, half-goat, and together they attempt to bring some changes to the community.Medford's rebellion spreads across the Island, and the Islanders must choose to join Medford in search of personal happiness or keep their own secrets hidden forever.